Analysis of Physical Condition Athletes in UNP Badminton Academy - Dapid Putra; Eval Edmizal; Donie; Juanda Putra (STKIP Pasundan, 2026)
This study aims to analyze the physical condition level of athletes at UNP Badminton Academy Padang. The research employed a descriptive quantitative method. The population consisted of 21 athletes, and total sampling was used, meaning all athletes were included as research samples. The athletes consisted of male and female players aged between 15–22 years. Data were collected using physical condition tests, including chin-up, push-up, 30-meter sprint, sit and reach, vertical jump, and beep test. The results showed that the overall physical condition of the athletes was categorized as very poor, with an average score of 2.5. All physical components, including strength, endurance, speed, flexibility, power, and cardiovascular endurance, were still below optimal levels. It can be concluded that the athletes’ physical condition needs significant improvement through structured and systematic training programs to support better performance in the future.